A Case of 22q11.2 Deletion Syndrome with Right Microphthalmia and Left Corneal Staphyloma. (December 2014) - Tarlan, Berçin; Kiratli, Hayyam; Kılıç, Esra; Utine, Eda; Boduroğlu, Koray
Abstract Background: A microdeletion in the chromosome 22q11.2 (DiGeorge or velocardiofacial syndrome) is the most common human deletion syndrome. Patients with 22q11.2 deletion may have a wide range of ocular findings but severe ocular involvement is uncommon. Here, we describe a 2-year-old boy who had growth retardation, developmental delay, right renal agenesis, ventricular septal defect and severe bilateral ocular anomalies. Materials and methods: The systemic and ocular findings and cranial magnetic resonance imaging study results were reviewed. Fluorescence in situ hybridization analysis was performed on his peripheral blood. Results: The patient presented with the oculodigital sign. On examination, he had severe right microphthalmia with no light perception and his left eye could not fix and follow. The left eye had anterior segment dysgenesis, mild sclerocornea, corneal staphyloma and congenital aphakia. Systemic findings included growth deficiency, microcephaly, micrognathia, ventricular septal defect, atrial septal defect and right renal agenesis. Fluorescence in situ hybridization analysis of this patient was significant for a heterozygous deletion covering DiGeorge critical region 2 and spanning a 250 kb region in the 22q11.2 locus. Conclusion: The 22q11.2 deletion syndrome may be associated with severe bilateral ocular malformations including microphthalmia, sclerocornea, corneal staphyloma, anterior segment dysgenesis and congenital aphakia. Corneal staphyloma might have resulted from the oculodigital phenomenon or increased intraocular pressure.